Biomimetic mineralizable collagen hydrogels for dynamic bone matrix formation to promote osteogenesis. Issue 15 (23rd March 2020) - Chen, Lu; Wu, Chengheng; Chen, Suping; Zhang, Yusheng; Liu, Amin; Ding, Jie; Wei, Dan; Guo, Zhenzhen; Sun, Jing; Fan, Hongsong
Abstract : Biomimetic mineralizable collagen hydrogels simulate the dynamic bone matrix mineralizing process via the synergy of cellular secretions, and form a microenvironment that promotes osteogenesis. Abstract : The simulation of the native bone matrix formation process is crucial for the construction of the cellular microenvironment for bone regeneration. However, it is still challenging to design bioactive materials that simultaneously mimic the composition and dynamic mineralization process of the bone matrix, let alone realize osteoinduction by a biomimetic dynamic microenvironment. In this study, we prepared a biomimetic mineralizable collagen hydrogel (CAV) and explored the effects of a dynamic mineralized matrix on the osteogenesis of stem cells both in vitro and in vivo . We showed the feasibility of the biomimetic CAV hydrogel to induce mineralization in simulated media including simulated body fluid (SBF), glycerol phosphate calcium salt hydrate (CaGP) solution and cell co-cultured systems. The participation of cells in the mineralization process is more likely to induce matrix remodeling due to the synergistic effects of CAV mineralization and cellular secretion, resulting in higher matrix strength. We also demonstrated that the biomimetic mineralized hydrogel could up-regulate osteogenic genes and protein expression of bone marrow mesenchymal stem cells (BMSCs), thus enhancing osteogenesis in vivo . The interactions between the mineralizable hydrogel and cells play an important role in regulating dynamic matrix mineralization and osteogenesis. Our findings prove that the biomimetic mineralizable hydrogel is a promising candidate for implantable orthopedic applications and provides essential implications for the future design of materials for bone regeneration.